Induced Autolysis of Engineered Yeast Residue as a Means to Simplify Downstream Processing for Valorization—A Case Study - Joana F. Fundo; Teresa Deuchande; Daniela A. Rodrigues; Lígia L. Pimentel; Susana S. M. P. Vidigal; Luís M. Rodríguez-Alcalá; Manuela E. Pintado; Ana L. Amaro (Fermentation, 2023)
The objective of this work was to study the efficiency of different autolysis processes, combining different temperatures and pH conditions, when applied to a genetically engineered yeast residue. The determination of the supernatants’ dry weight showed that the autolysis time could be reduced to half, from 4 to 2 h, if the residue pH was increased from 5 to 8 at 50 °C (18.20% for 4 h and 18.70% for 2 h with a higher pH). This result allowed us to select a short autolysis time to proceed with the second part of the experiments. The application of this faster induced autolysis process enabled us to obtain supernatants with higher concentrations of relevant compounds, such as some amino acids and minerals. An increase in leucine (of around 7%), aspartic acid, valine, phenylalanine, isoleucine and serine (approximately 2%) was observed in the autolyzed samples, when compared to the untreated ones. Also, regarding minerals, the autolysis process allowed us to obtain significantly higher amounts of potassium in the treated samples’ supernatants. This work allowed the selection of a fast and low-cost induced autolysis process for synthetic biotechnology-derived spent yeast residue to attain a product rich in high-value compounds, which can be used in commercial applications, for example, as an animal feed additive.